Quantum mechanics - Auletta, Gennaro, 1957- (Cambridge University Press, 2009)
The important changes quantum mechanics has undergone in recent years are reflected in this new approach for students. A strong narrative and over 300 worked problems lead the student from experiment, through general principles of the theory, to modern applications.